2014
DOI: 10.1136/annrheumdis-2013-204867
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in patients with rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis: results from the Danish nationwide DANBIO registry

Abstract: Background/purposeEarly diagnosis of inflammatory rheumatic diseases is important in order to improve long-term outcome. We studied whether delay in diagnosis (time between onset of symptoms and establishment of diagnosis) in patients with rheumatoid arthritis (RA), psoriatic arthritis (PSA) and ankylosing spondylitis (AS) changed from year 2000 to 2011.MethodsMonth and year of initial symptoms and diagnosis, gender, hospital, year of birth and date of first data entry were obtained for 13 721 patients with RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 35 publications
11
119
0
6
Order By: Relevance
“…A recent prospective, multicenter controlled study demonstrated that after specific spondyloarthritis-aimed training, a general practitioner's consideration to refer patients with symptoms of axial and peripheral spondyloarthritis increased by more than 40% [43]. As discussed above, data from the DANBIO registry also suggest marked improvements in the time from symptom onset to diagnosis over recent years [24]. Furthermore, data from two large UK centers show that reported new cases of AS increased by 51% between 2009 and 2013 versus the preceding 5 years [25].…”
Section: Increasing Knowledge and Awareness For Patients And Physiciansmentioning
confidence: 82%
See 1 more Smart Citation
“…A recent prospective, multicenter controlled study demonstrated that after specific spondyloarthritis-aimed training, a general practitioner's consideration to refer patients with symptoms of axial and peripheral spondyloarthritis increased by more than 40% [43]. As discussed above, data from the DANBIO registry also suggest marked improvements in the time from symptom onset to diagnosis over recent years [24]. Furthermore, data from two large UK centers show that reported new cases of AS increased by 51% between 2009 and 2013 versus the preceding 5 years [25].…”
Section: Increasing Knowledge and Awareness For Patients And Physiciansmentioning
confidence: 82%
“…For PsA, an average delay in diagnosis of 5 years was reported in the MAPP study [7]. Although data from the Danish nationwide DANBIO registry suggest distinct improvements in time from symptom onset to diagnosis in both PsA and AxSpA over the last two decades [24], such changes were not seen in a recent UK study [25] and therefore require further investigation in future studies.…”
Section: Reducing Time To Diagnosismentioning
confidence: 82%
“…The inclusion criteria were original articles in which SpA was the main subject, which analyzed delay in diagnosis and included women. We excluded papers with PsA patients because, although this disease also shows diagnosis delay, it is less than that found in AS 4 , probably due to the presence of psoriasis in two-thirds of patients prior to arthritis. In addition, papers were excluded if they did not fulfill the study criteria or consisted of editorials, reviews, case studies, questionnaires, or diagnostic/therapeutic techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Radiological alterations are slow to appear and hence underrecognition or considerable diagnostic delay has been frequent. As a result of the discovery of the association with HLA-B27, the development of classification criteria for the different clinical forms, and probably, closer attention, delay has been reduced in recent years 4 .…”
mentioning
confidence: 99%
“…Data for early identification of PsA and SpA were discussed [11], as was predictors of poor outcomes [12] [13], consequences of diagnostic delay [14], the relationship between skin involvement and PsA risk [15] [16], and available and emerging agents within pathways such as PDE4, IL-12, IL-23, and IL-17.…”
Section: Introductionmentioning
confidence: 99%